Hubungan Pengetahuan dan Sikap tentang Core Values ASN BerAKHLAK terhadap Perilaku Penerapan Core Values ASN BerAKHLAK pada ASN di lingkungan Badan Kepegawaian Daerah Kabupaten Lumajang - Aksanul Inam (Sanskara Manajemen Dan Bisnis, 2023)
The Lumajang Regency Government (Pemkab) followed this up by conducting outreach to all ASN on April 12 2022. The population in this study were employees in the BKD environment, with the sample used in this research being all BKD employees. The sampling technique is a non-probability sampling technique, namely census / total sampling. The number of samples studied were 70 respondents. The sampling period is 19-31 August 2022. The analysis used in this study is univariate analysis in the form of a frequency distribution. The variables studied, namely knowledge, attitudes and behavior related to the implementation of the Core Values BerAKHLAK. In addition to univariate analysis, bivariate analysis was also carried out. The results of the study based on univariate analysis showed that 75.7% of BKD ASNs had a good level of knowledge, 97.2% of BKD ASNs had a good attitude, but only 52.8% of BKD ASNs had good behavior.